An Electroactive Pure Organic Room‐Temperature Phosphorescence Polymer Based on a Donor‐Oxygen‐Acceptor Geometry. Issue 5 (30th November 2020) - Liu, Xinrui; Yang, Liuqing; Li, Xuefei; Zhao, Lei; Wang, Shumeng; Lu, Zheng‐Hong; Ding, Junqiao; Wang, Lixiang
Abstract: An electroactive room‐temperature phosphorescence (RTP) polymer has been demonstrated based on a characteristic donor‐oxygen‐acceptor geometry. Compared with the donor–acceptor reference, the inserted oxygen atom between donor and acceptor can not only decrease hole‐electron orbital overlap to suppress the charge transfer fluorescence, but also strengthen spin‐orbital coupling effect to facilitate the intersystem crossing and subsequent phosphorescence channels. As a result, a significant RTP is observed in solid states under photo excitation. Most noticeably, the corresponding polymer light‐emitting diodes (PLEDs) reveal a dominant electrophosphorescence with a record‐high external quantum efficiency of 9.7 %. The performance goes well beyond the 5 % theoretical limit for typical fluors, opening a new door to the development of pure organic RTP polymers towards efficient PLEDs. Abstract : A donor‐oxygen‐acceptor geometry has been demonstrated for the design of electroactive pure organic room‐temperature phosphorescence polymers, whose PLEDs achieve a promising EQE of 9.7 %.